INTERNALIZATION OF HIFZ AL-‘AQL THROUGH RELIGIOUS LITERACY ON SOCIAL MEDIA FOR STRENGTHENING STUDENTS’ CRITICAL THINKING IN FIQH LESSONS - Erdiyan Saputra; Ahmad Muhtar Syarofi; Ahmad Khoiri (Jurnal Ikhtibar Nusantara, 2026)
The development of social media provides easy access to various religious information; however, it also has the potential to cause misunderstandings in interpreting Islamic teachings. This study aims to analyze the internalization of hifz al-‘aql through religious literacy on social media in fiqh learning. This research employs a qualitative approach using a library research method. The data were obtained from various literature sources such as books and journal articles relevant to the study of maqasid al-shari’ah, digital literacy, and Islamic education. The results indicate that the internalization of hifz al-‘aql can be implemented through strengthening digital religious literacy that encourages students to understand religious arguments rationally, analyze religious information, and think critically when dealing with various religious issues on social media.